Meningkatkan Percaya Diri Melalui Layanan Konseling Kelompok - Sulistiyani Sulistiyani (Jurnal Prakarsa Paedagogia, 2018)
The aim of the study was to apply group counseling services to improve Class IX confidence. SMP 1 Cluwak in Semester I Academic Year 2017/2018. Research Hypothesis: Suspected Group Counseling Services Can Improve Students' Confidence in Class IX.A SMP 1 Cluwak Semester I Academic Year 2017/2018. This research was conducted in Class IX.A SMP 1 Cluwak in Semester I Academic Year 2017/2018. The subjects in this study were 7 students, students of class IX.A in the academic year who were in the severe problem category. PTBK: Suspected Group Counseling Services Can Improve Student Confidence Class IX.A SMP 1 Cluwak in Semester I Academic Year is said to be true, this is evident by an increase in each cycle. And 2) Increasing group counseling services in reducing the confidence of Class IX.A SMP 1 Cluwak students in Semester I of Academic Year, the lower, the confidence that occurs in Class IX.A Cluwak Pati 1 Middle School students in Semester I 2017/2018 Academic Year. PTBK Implications: Results of PTBK conclusions stating that there is an Effort to Increase Confidence through Class IX.A Group Counseling Services in SMP Negeri 1 Cluwak Pati Semester I Academic Year is proven true, so the confidence that occurs in Class IX.A SMP Negeri 1 Cluwak students Semester I Academic Year is increasing, this is evident by the increase in each cycle.